PENYULUHAN DAN PELATIHAN FISIOTERAPI PADA BALITA DI POSYANDU BALITA SERUNI XII PONCOL KOTA PEKALONGAN - Nur Susanti; Anggun Rahmawati Putri (LPPM Universitas Pekalongan, 2020)
Babies are children with an age range of 0-12 months. Infancy is the first period of critical life. During infancy, children will adapt to the environment, changes in blood circulation, and body organs begin to work. From the observation process of identifying physiotherapy problems in infants by lecturers and students of D-III Department of Physiotherapy, Faculty of Health, Pekalongan University conducted by interviewing Posyandu cadres, it was found that the most common problems experienced by toddlers was a decrease in appetite in toddlers. Situation analysis in the form of observations made by the whole team in the environment of activities in Posyandu Balita Seruni XII Poncol, Pekalongan City was in form of interviews to Posyandu cadres. The process of observing the identification of physiotherapy problems in toddlers used an assessment method. The purpose of this activity was to increase the knowledge and understanding of cadres and parents about the role of physiotherapy in toddlers, especially in increasing appetite in children. The solution offered by the team was to use the counseling and training methods to improve appetite in toddlers with baby massage and neurostructure techniques. The implementations of counseling and training activities were attended by seventeen toddlers accompanied by their mothers. Before counseling and training process, the toddlers’ mothers were given a pre-test and post-test that became a benchmark for toddlers’ mothers understanding about counseling and training conducted. The results of the pre-test and post-test proved that the level of understanding of mothers under five increased after being given counseling and training in physiotherapy. It can be concluded that after being given counseling and physiotherapy training, the level of toddlers’ mothers understanding in increasing the appetite of infants was increased.